Evaluasi Rasionalitas Penggunaan Obat Antihipertensi di Puskesmas Siantan Hilir Kota Pontianak Tahun 2015 - Untari, Eka Kartika; Agilina, Alvani Renata; Susanti, Ressi (Pharmaceutical Sciences and Research, 2018)
Hypertension is widely known as cardiovascular disease. In addition to resulting heart failure, hypertension can result in kidney failure and cerebrovascular disease. This study was aimed to determine the percentage of treatment rationality of hypertensive patient treatment outpatient in Puskesmas Siantan Hilir Pontianak 2015 which includes the appropriate indication, appropriate drug, appropriate patient, and appropriate dose based on the guideline JNC 7. This study was cross-sectional study using medical records of outpatient hypertension patients in 2015. The total of sample analyzed in this research were 92 medical records of hypertension patients from 118 medical records. The percentage of using the angiotensin converting enzym inhibitor (captopril) was 47.46%; calcium channel blocker (amlodipine) was 34.75%; thiazid diuretic (hydrochlorothiazid) was 16.10%; loop diuretic (furosemid) was 0.85%; and potassium sparing (spironolactone) was 0.85%. The rasionality of hypertensive therapy in patients in this study were 100% appropriate indication; 70.65% appropriate drug; 100% appropriate patient; and 98.91% appropriate dose. The conclusion of this study is that overall treatment that meets all four rational treatment criterias was 69.56%.